2018
DOI: 10.18203/2349-3291.ijcp20182480
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity among urban and rural school going adolescents of Vadodara, India: a comparative study

Abstract: Background: Obesity is a major global problem among children. India has paradox of having both undernutrition and obesity as a major problem. This epidemic of obesity is also affecting rural population. It has both short   and long term adverse health outcome.Methods: The present study is a cross-sectional, observational and questionnaire-based study conducted in urban and rural school going adolescents.Results: 188 subjects (89 rural and 99 urban school) school were enrolled. 17.6%(33), 20.2%(38), 59%(111) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 13 publications
4
17
0
Order By: Relevance
“…Wang et al (2018) also observed that the prevalence of overweight in urban areas was higher than in rural areas (9.3% versus 7.1%) while studies by Pathak et al and Alok et al showed positive correlation between type of residence and BMI categories which were statistically significant. [15][16][17] In the present study higher number of males (17.5%) was overweight or obese than a female (18.4%) which is similar to NFHS-4 data. 18 In our study overweight and obesity was found more in adolescents from nuclear family than who were from joint family, however, findings were not statistically significant.…”
Section: Discussionsupporting
confidence: 86%
“…Wang et al (2018) also observed that the prevalence of overweight in urban areas was higher than in rural areas (9.3% versus 7.1%) while studies by Pathak et al and Alok et al showed positive correlation between type of residence and BMI categories which were statistically significant. [15][16][17] In the present study higher number of males (17.5%) was overweight or obese than a female (18.4%) which is similar to NFHS-4 data. 18 In our study overweight and obesity was found more in adolescents from nuclear family than who were from joint family, however, findings were not statistically significant.…”
Section: Discussionsupporting
confidence: 86%
“…11 Whereas Pathak S et al, study the same was 15.78% in boys and 3.92% in girls. 12 In present study the prevalence of underweight was 17.12% in boys and 16.13% in girls with overall prevalence was 16.66%. In contrast, Sanghamitra P et al, study same was 5.18% in boys and 1.12% in girls with overall underweight prevalence was 2.54%.…”
Section: Discussionsupporting
confidence: 46%
“…Whereas Pathak S et al, study done in rural area of India found prevalence of overweight and obese was 6.7% and 2.2%, respectively with combined prevalence of overweight and obesity was 8.98%. 12 Another similar study by Prashanth SV et al, done in high schools of rural and urban areas of Davangere, Karnataka, India mentioned combined prevalence of overweight and obesity in high schools of rural areas was 7.1%. 13 A systematic review on Epidemiology of childhood overweight and obesity in India done by Harish R et al, described overall prevalence of overweight and obesity ranges between 3 to 24.7% and 1.5 to 14% in India.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations